Quiz show [videorecording (DVD)] - Redford, Robert; Turturro, John, 1957-; Morrow, Rob; Fiennes, Ralph; Goodwin, Richard N. (Hollywood Pictures Home Video, 1995)
Fame and fortune become a hotbed of scandal when a Washington investigator uncovers corruption beneath the TV's hottest quiz show's glittering facade. The scandal implicates both the wildly popular champion and the disgruntled ex-champ.